EFFECTIVENESS OF BOOKLET AND VIDEO AS A PRENATAL HEALTH EDUCATION MEDIA FOR READINESS AND DECREASE IN CHILDBIRTH ANXIETY - Rohmi Handayani; Siti Yulaikah (Universitas Andalas, 2019)
Pregnancy and Childbirth are physiological. But normal pregnancy and childbirth can turn into pathology. One of the ways to prevent delays in handling is through the readiness of childbirth by means of health education using media and video media. Analyzing the differences in the effectiveness of Prenatal health education using Booklet and Video media in reducing anxiety and increasing maternity readiness. This type of research is Quasy Experiment with one group pretest posttest design research design. The population in this study were all pregnant women in the working area of the South Klaten Puskesmas in the February to September 2019 period with a sampling quota of 60 pregnant women, namely 30 booklet groups and 30 video groups. Data analysis uses paired t-test, Wilcoxon and Mann Whitney. Prenatal health education using the Media Booklet is effective in reducing anxiety and increasing readiness to face labor with a p value <0.05. Prenatal health education using Video Media is effective in decreasing the increase in readiness to face childbirth with a p value <0.05. Prenatal health education using the Booklet media is more effective compared to Video media in reducing anxiety and increasing labor readiness with a p value <0.05